Oxidation of amino acids by peracetic acid: Reaction kinetics, pathways and theoretical calculations - Du, P. (2021)
Reactions of MET and HIS with PAA followed second-order kinetics with rate constants of 4.6 ± 0.2, and 1.8 ± 0.1 M−1⋅s−1 at pH 7, respectively. The reactions were faster at pH 5 and 7 than at pH 9 due to PAA speciation. Low concentrations of H2O2 coexistent with PAA contributed little to the oxidation of amino acids. The primary oxidation products of amino acids with PAA were [O] addition compounds on the reactive sites at thiol, thioether and imidazole groups. Theoretical calculations were applied to predict the reactivity and regioselectivity of PAA electrophilic attacks on amino acids and improved mechanistic understanding. As an oxidative disinfectant, the reaction of PAA with organics to form byproducts is inevitable; however, this study shows that PAA exhibits lower and more selective reactivity towards biomolecules such as amino acids than other common disinfectants, causing less concern of toxic disinfection byproducts. This attribute may allow greater stability and more targeted actions of PAA in various applications.